Two‐stage autotransplantation of the human submandibular gland: First long‐term results. (4th February 2016) - Burghartz, Marc; Ginzkey, Christian; Hackenberg, Stephan; Hagen, Rudolf
Abstract : Objectives/Hypothesis: Xerostomia is still one of the predominant side effects of radiotherapy (RT). This study investigates long‐term results of a new surgical method that spares the submandibular gland from radiation. Study Design: Eleven patients with head and neck carcinoma were enrolled in the study. In five patients 6‐month follow‐up testing, and in two of these patients 12‐month follow‐up testing was performed. Methods: The submandibular gland was transplanted to the patients forearm for the time of radiation. Two months after completion of RT, the gland was retransplanted to the neck. Patients saliva flow was tested via the Saxon test, and patients had to answer the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire–Head and Neck 35 and visual analog scale. Results: Following the two‐stage autotransplantation, xerostomia was reduced in the long term due to improved saliva production of the reimplanted gland. Conclusions: Whether this promising novel approach is a reliable treatment option for RT patients in general should be evaluated in further studies. Level of Evidence: 4. Laryngoscope, 126:1551–1555, 2016